1995
DOI: 10.1037/0021-843x.104.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Testing a tripartite model: I. Evaluating the convergent and discriminant validity of anxiety and depression symptom scales.

Abstract: L.A. Clark and D. Watson (1991) proposed a tripartite model that groups symptoms of depression and anxiety into 3 subtypes: symptoms of general distress that are largely nonspecific, manifestations of somatic tension and arousal that are relatively unique to anxiety, and symptoms of anhedonia and low Positive Affect that are specific to depression. This model was tested in 5 samples (3 student, 1 adult, and 1 patient sample) using the Mood and Anxiety Symptom Questionnaire (MASQ; D. Watson & L. A. Clark, 1991)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
1,029
6
12

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,160 publications
(1,111 citation statements)
references
References 29 publications
48
1,029
6
12
Order By: Relevance
“…To obtain large variability in negative attentional bias, participants with minimal and severe depressive symptoms were sampled from the Ghent University research participant pool based on a prescreening measure (Mood and Anxiety Symptom Questionnaire; Watson, Clark, Weber, Assenheimer, Strauss, & McCormick, 1995). At testing, 40 participants (33 women; 18-29 years) reported a broad range of depressive symptom severity levels (range: 0-42, M=13.28, SD=9.15) on the Beck Depression Inventory-II (Beck, Steer, & Brown, 1996;Van der Does, 2002).…”
Section: Methods Participantsmentioning
confidence: 99%
“…To obtain large variability in negative attentional bias, participants with minimal and severe depressive symptoms were sampled from the Ghent University research participant pool based on a prescreening measure (Mood and Anxiety Symptom Questionnaire; Watson, Clark, Weber, Assenheimer, Strauss, & McCormick, 1995). At testing, 40 participants (33 women; 18-29 years) reported a broad range of depressive symptom severity levels (range: 0-42, M=13.28, SD=9.15) on the Beck Depression Inventory-II (Beck, Steer, & Brown, 1996;Van der Does, 2002).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Over the years, substantial evidence has accumulated suggesting that depression is associated with diminished hedonic capacity and, more generally, dysfunction in an approach-related system subserving positive affect and motivated behavior. First, studies have shown that depression is characterized by low selfreported positive affect and reduced engagement with the environment (e.g., de Beurs et al, 2007;Watson et al, 1995). Moreover, reduced positive affect have been concurrently and prospectively linked to depression in adult samples (Clark et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…While safety and pharmacodynamics were the main objectives of this study, symptom changes were measured on HAM‐D‐17 and MASQ (Watson et al., 1995). A cross‐sectional analysis of symptom severity measured using MASQ showed correlation with cortisol levels (Veen et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Study drug was administered for only one week. MASQ was not designed for symptom change measurement (Watson et al., 1995), and there are only sparse data showing score changes during antidepressant treatment (Dichter et al., 2005; Tomarken et al., 2004). Baseline differences between regimens on current episode duration, prior antidepressant use or recurrent MDD diagnosis could have confounded the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation